Nationalism and Minorities in the Ottoman Balkans: Greek Discourses on the Eastern Crisis (1875–1878) - Iliadis, Christos (The Historical Review/La Revue Historique, 2019)
This article focuses on how the Eastern Crisis of 1875–1878 and the Slavic revolts were interpreted in Greece, given its national aspirations and its relationship with the Orthodox people of the Balkans. The analysis draws on the Athenian press and parliamentary minutes of the time, and rather than focusing on the diplomatic developments follows instead the social discourses on and dominant interpretations of the Slavs and Bulgarians after the Balkan uprisings as well as the dilemmas faced by Greece. It explores a moment in the discursive shift, which introduced an ethno-racial language within the Greek kingdom that began to replace the portrayal of Hellenism as an ecumenical ideology with one of a more exclusive and nationalistic character. It thus shows how the events sharpened the division between Hellenism and Slavism.